Mandibular Morphological Changes According to Functional Occlusal Status: A Descriptive Radiomorphometric Study - Arif Keskin; Mehmet Feryüz Öksüz; Hatice Zehra Bodur Güney; Tayfun Aygün (Middle Black Sea Journal of Health Science, 2026)
Objective: This study aimed to measure the gonial angle (GA) and the ramus height/condyle height (RH/CH) ratio in five groups defined according to the functional occlusal status of the mandibular molar teeth, using open-access panoramic radiography databases, and to establish descriptive reference values for these groups.Methods: Digital panoramic radiographs from two open-access, fully anonymized databases (the Children's Dental Panoramic Radiographs Dataset for the pediatric group; the Tufts Dental Database for the adult groups) were evaluated retrospectively and cross-sectionally. Of 1093 radiographs screened, 214 individuals (428 mandibular regions) meeting the inclusion criteria were divided into five groups by the functional occlusal status of the mandibular first permanent molar: pre-functional pediatric (Group 1, n=31), functional pediatric (Group 2, n=36), adult functional (Group 3, n=40), partial molar loss (Group 4, n=73), and total edentulism (Group 5, n=34). GA and the RH/CH ratio were measured with ImageJ as magnification-independent parameters. Between-group comparisons used a linear mixed-effects model. Because the database and group effects were confounded, inferential evaluation was primarily restricted to groups within the same database.Results: Measurement reliability was good at both intra- and inter-observer levels (all ICC > 0.80). GA was highest in the totally edentulous group (124.58° ± 7.03), which had a significantly higher GA than each of the other four groups (p<0.001 for all; eta-squared=0.168, large effect). Within the Tufts database, GA increased significantly from adult functional dentition toward partial molar loss (p=0.010) and total edentulism (p<0.001), the most pronounced increase being in total edentulism. Within the pediatric database, no significant difference was found between the pre-functional and functional groups (GA p=0.227; RH/CH p=0.447). The RH/CH ratio was less sensitive in distinguishing groups (epsilon-squared=0.035, small effect), with a significant difference only between partial molar loss and total edentulism (p<0.001).Conclusion: The findings suggest that GA is sensitive to functional occlusal status from the partial tooth-loss stage onward, with the most pronounced widening in total edentulism; the contribution of molar function to the early developmental period appears limited. As the RH/CH ratio alone is weaker than GA in group discrimination, joint evaluation of the two parameters is recommended. Owing to the cross-sectional design, the absence of individual age and sex data, and the database–group confounding, the findings should be interpreted as descriptive rather than causal.